Application of adaline networks in an efficient procedure for measuring fundamental reactive power and budeanu reactive power in distorted electrical systems - Alcántara, Francisco J. (2025)
This work introduces an efficient procedure for measuring reactive power in single-phase systems in the presence of harmonic distortion. The measurement of reactive power is based on the application of the ADALINE network to estimate the voltage harmonics and, subsequently, to define a certain single-phase magnitude whose average value provides the reactive measurement. Two definitions of the reactive power have been considered: the reactive power of the fundamental harmonic Q1 and the well-known Budeanu reactive power QB, which is physically meaningless according to many studies. In addition, the proposed neural procedure of calculating the two reactive powers has been compared with other traditional methodologies for calculating Q, specifically, the application of FFT to voltage and current and the 90° voltage delay method. The new methodology has been applied to two laboratory case studies. A first standard case of small power, which has allowed to compare the different definitions of reactive power with each other and the experimental measurements with the theoretical results. The second case study was three higher power loads fed from the 220 V mains power to test the accuracy of the different Q measurement procedures. Finally, from the results, it can be concluded that the proposed procedure presents better performance compared to traditional procedures. In addition, the reactive power Q1 takes very different values than QB in the first laboratory case, which confirms the true physical sense of the first reactive power versus the second.